Development and trials of a novel deep-sea multi-joint autonomous underwater vehicle. (1st December 2022) - Liu, Kexian; Wang, Haoyu; Xu, Xuehan; Song, Tianshu; Meng, Qinghao
Abstract: To realize fine exploration in the deep sea, this paper designed a highly maneuverable multi-joint autonomous underwater vehicle (MJ-AUV). MJ-AUV is composed of three cabins in series, which are connected mechanically and electrically through two joint systems. The rotation of the joints drives the deformation of MJ-AUV, thereby realizing a variety of maneuvering modes. Each connecting joint is driven by a two-stage bevel gear, which is compact in structure and has good strength and rigidity, and can drive the cabins to achieve two degrees of freedom (i.e., pitch and yaw) motion. Computational fluid dynamics (CFD) technology was used to build a numerical pool and calculate the added mass coefficient and drag coefficient of each cabin. The kinematics model of MJ-AUV was established and the force analysis was carried out. On this basis, the simulation environment was built through computational multi-body dynamics (MBD) software MSC Adams, which was used to systematically analyze the multiple motion states of MJ-AUV. Lake and sea trials conducted in Thousand Islet Lake, the South China Sea, Qingdao Coast, and other places have validated the actual performance of the designed MJ-AUV, including cruising mode, vertical profile motion, deep diving and water surface motion. Highlights: A novel multi-joint autonomous underwater vehicle (MJ-AUV) is designed. A joint system with two rotational freedom is designed to connect the cabins. The method of kinematic and force analysis of MJ-AUV are presented. The lake and sea trials are conducted to validate the motion performance of MJ-AUV. The MJ-AUV has great mobility and can work at a depth of 1000 m.